Water quality and breeding habitats of anopheline mosquito in northwestern Thailand - Ampornpan Kengluecha (2018)
Malaria transmission is dependent upon many hydrology-driven ecological factors that directly affect the vectorial competence, including the presence of suitable habitats for the development of anopheline larvae. Larval habitats were identified and characterized at three malaria endemic villages (Ban Khun Huay, Ban Pa Dae, and Ban Tham Seau) in Mae Sot district, Tak Province, in northwestern Thailand between July 2002 and June 2003. The Global Positioning System (GPS) was used to provide precise locational data for the spatial distribution of anopheline mosquito larvae and their habitats. Ten habitat categories were identified. Eighteen adult Anopheles species were identified from larvae in all the surveyed habitats. An. minimus was the most common species throughout the year. The relationship between eight abiotic variables (temperature, hardness, carbon dioxide, dissolved oxygen, nitrate, phosphate, silica and pH) and the abundance of four major species of malaria vectors (An. (Cel.) dirus, An. (Cel.) minimus, An. (Cel.) maculatus, and An. (Cel.) sawadwongporni), and six species of non-vectors (An. (Cel.) kochi, An. (Cel.) jamesii, An. (Ano.) peditaeniatus, An. (Ano.) barbirostris, An. (Ano.) campestris, and An (Cel.) vagus) larvae was investigated. The results from the multiple regression models suggest that hardness, water temperature and carbon dioxide are the best predictor variables associated with the abundance of An. minimus larvae (p<0.001); water pH for An. dirus larvae (p<0.001); temperature and pH for An. kochi larvae (p<0.01); temperature and silica concentration for An. jamesii larvae (p<0.001); dissolved oxygen and silica concentration for An. campestris larvae (p<0.001); and pH and silica concentration for An. vagus larvae (p<0.001). We could not identify key environmental variables for An. maculatus, An. sawadwongporni, An. peditaeniatus, and An. barbirostris.